2009
DOI: 10.1017/s0022149x09232342
|View full text |Cite
|
Sign up to set email alerts
|

Predatory activity of the fungi Duddingtonia flagrans, Monacrosporium thaumasium, Monacrosporium sinense and Arthrobotrys robusta on Angiostrongylus vasorum first-stage larvae

Abstract: Angiostrongylus vasorum is a nematode that parasitizes domestic dogs and wild canids. We compared the predatory capacity of isolates from the predatory fungi Duddingtonia flagrans (AC001), Monacrosporium thaumasium (NF34), Monacrosporium sinense (SF53) and Arthrobotrys robusta (I31) on first-stage larvae (L1) of A. vasorum under laboratory conditions. L1 A. vasorum were plated on 2% water-agar (WA) Petri dishes marked into 4 mm diameter fields with the four grown isolates and a control without fungus. Plates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
0
31
0
4
Order By: Relevance
“…Braga et al 10 demonstrated that AC001 grown in Petri dishes containing a solid culture (2% WA) did prey on and consequently destroyed 80.3% of A. vasorum L 1 at the end of 7 days. However, comparing this predatory activity with the observation in the present study, it can be noted that the efficiency (74.5%) in this same strain was similar since the predation of larvae occurred after 24h.…”
Section: Rev Soc Bras Med Trop 46(1):108-110 Jan-feb 2013mentioning
confidence: 99%
See 1 more Smart Citation
“…Braga et al 10 demonstrated that AC001 grown in Petri dishes containing a solid culture (2% WA) did prey on and consequently destroyed 80.3% of A. vasorum L 1 at the end of 7 days. However, comparing this predatory activity with the observation in the present study, it can be noted that the efficiency (74.5%) in this same strain was similar since the predation of larvae occurred after 24h.…”
Section: Rev Soc Bras Med Trop 46(1):108-110 Jan-feb 2013mentioning
confidence: 99%
“…Duddingtonia flagrans is considered the most promising nematode-trapping species in the control of nematodiasis in domestic animals due to its large chlamydospore production. In laboratory conditions, different fungal isolates of D. flagrans have previously been successfully utilized to control gastrointestinal nematodes in domestic animals, especially the isolates AC001 and CG722 9,10 . However, this is the first report comparing the in vitro predatory activity of the conidia of different isolates of the fungus D. flagrans on first-stage (L 1 ) larvae of A. vasorum.…”
mentioning
confidence: 99%
“…Nesse contexto, sugere-se a empregabilidade dos fungos nematófagos Duddingtonia, Monacrosporium e Artrobotrys, cuja capacidade predatória sobre L 3 de nematoides parasitas gastrintestinais com potencial zoonótico tem sido comprovada [7][8][9] . Todavia, a capacidade predatória destes fungos nunca tinha sido testada sobre de L 3 Os resultados obtidos no presente trabalho confirmam trabalhos anteriores da eficiência dos fungos nematófagos Duddingtonia flagrans (AC001), Monacrosporium thaumasium (NF34) e Artrobotrys robusta (I-31) no controle de larvas de nematoides potencialmente zoonóticas.…”
Section: Referências Suporte Financeiro Conflito De Interesseunclassified
“…Fungos predadores de nematoides é certamente o grupo mais estudado e que apresenta o maior potencial na destruição das formas infectantes de nematoides parasitos gastrintestinais de animais e humanos 8 . As espécies de fungos nematófagos Duddingtonia flagrans, Monacrosporium thaumasium e Artrobotrys robusta são identificadas como predadoras e têm sido estudadas como agentes controladores biológicos de nematoides potencialmente zoonóticos 9 .…”
unclassified
“…Contudo, os fungos nematófagos têm apresentado resultados promissores no combate aos geo-helmintos presentes no ambiente contaminado. As espécies de fungos nematófagos Duddingtonia flagrans, Arthrobotrys robusta e Monacrosporium sinense são identificadas como predadoras e têm sido estudadas como agentes controladores biológicos de nematoides potencialmente zoonóticos, entretanto, podem existir diferenças no mecanismo de ação desses fungos sobre os distintos gêneros de nematoides 8 Foram observados os seguintes percentuais de redução de L 3 de S. venezuelensis: 93% (AC001); 77,2% (I-31) e 65,2% (SF53). A presença das L 3 de Strongyloides venezuelensis nas placas de Petri contendo AA2% foi essencial para a formação das armadilhas pelos isolados fúngicos, uma vez que, esse meio de cultura é pobre em nutrientes (Figuras 1A e B).…”
unclassified